Bash Quick Start Guide - Tom Ryder (Packt Publishing, 2018)
Bash Quick Start Guide is the go-to resource for anyone looking to effectively use and master Bash scripting. You will learn to navigate the Bash environment, write efficient scripts, and leverage Bash's powerful features to automate tasks and tailor your workflows. This book provides clear explanations, practical examples, and helpful insights to empower you in your projects.What this Book will help me doUnderstand the role and utility of the Bash shell in system administration and programming tasks.Learn to effectively interact with the Bash command line and its essential feature set.Gain proficiency in creating, managing, and executing Bash scripts to automate repetitive tasks.Master the art of filtering and transforming text and data processing directly within Bash.Develop the skills to configure and personalize the Bash environment for optimized workflows.Author(s)None Ryder is an experienced software developer and Linux system administrator with a passion for teaching actionable knowledge. With years of experience in shell scripting and automating tasks in Linux, they bring in-depth understanding and practice-tested techniques to their writing. None focuses on making complex technical concepts accessible, ensuring the reader's success at every step.Who is it for?This book is perfect for professionals who regularly use Unix and Linux systems and seek to enhance their command-line automation expertise. Readers with familiarity in other scripting languages like Python or PHP will find the book helps them smoothly adapt to Bash. System administrators, devops engineers, and developers aiming to boost their shell scripting efficiency will greatly benefit. If you're looking to harness the full potential of the Bash shell to streamline your tasks and workflows, this book is designed for you.